The Effects of Virtual Reality on Procedural Pain and Anxiety in Pediatrics: A Systematic Review and Meta-Analysis - Nordgård, Rikke; Låg, Torstein (Frontiers in Virtual Reality, 2021)
Distraction and procedural preparation techniques are frequently used to manage pain and anxiety in children undergoing medical procedures. An increasing number of studies have indicated that Virtual Reality (VR) can be used to deliver these interventions, but treatment effects vary greatly. The present study is a systematic review and meta-analysis of studies that have used VR to reduce procedural pain and anxiety in children. It is the first meta-analytic assessment of the potential influence of technical specifications (immersion) and degree of user-system interactivity on treatment effects. 65 studies were identified, of which 42 reported pain outcomes and 35 reported anxiety outcomes. Results indicate large effect sizes in favor of VR for both outcomes. Larger effects were observed in dental studies and studies that used non-interactive VR. No relationship was found between the degree of immersion or participant age and treatment effects. Most studies were found to have a high risk of bias and there are strong indications of publication bias. The results and their implications are discussed in context of these limitations, and modified effect sizes are suggested. Finally, recommendations for future investigations are provided.